SYSTEMIC LUPUS ERYTHEMATOSUS AND OPPORTUNISTIC INFECTIONS: PREVALENCE, CLINICAL FEATURES - O N Egorova; R M Balabanova; E G Sazhina; O N Egorova; R M Balabanova; E G Sazhina (Современная ревматология)
Current therapy for systemic lupus erythematosus (SLE) envisages long-term treatment with cytostatic drugs, which is frequently accompanied by activation of comorbid infection, including viral one. Objective: to determine the clinical features of SLE complicated by herpesviral infection. Subjects and methods. Sixty-seven patients with a 1-to-7 history of SLE who received first-line therapy were examined. Results. The analysis of the history data and the results of a serological survey identified 3 groups of patients: 1) 35 patients with viral infection, of them 9 had mixed viral-and-bacterial infections; 2) 14 with bacterial infections and 3) 18 patients without viral-and-bacterial complications. The analysis of clinical symptoms established a correlation of high titers of antibodies to cytomegalovirus (CMV) and Epstein-Barr virus (EBV) with symptoms, such as fever, arthritis, lymphadenopathy, carditis, hepatomegaly and erythema migrans eruption. However, having the similar clinical manifestations, CMV and EBV infections had some organ specificity. In SLE, concomitant comorbid infection, viral infection in particular, contributed to the development of the clinical picture polymorphism with the protracted, remitting inflammatory process and the inadequate efficiency of glucocorticoid and immunosuppressive therapy.